2013
DOI: 10.1158/1078-0432.ccr-12-3554
|View full text |Cite
|
Sign up to set email alerts
|

Murine Microenvironment Metaprofiles Associate with Human Cancer Etiology and Intrinsic Subtypes

Abstract: Purpose Ionizing radiation is a well established carcinogen in rodent models and a risk factor associated with human cancer. We developed a mouse model that captures radiation effects on host biology by transplanting unirradiated Trp53 null mammary tissue to sham or irradiated hosts. Gene expression profiles of tumors that arose in irradiated mice are distinct from those that arose in naïve hosts. We asked whether expression metaprofiles could discern radiation-preceded human cancer or be informative in sporad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 49 publications
(56 reference statements)
4
27
0
Order By: Relevance
“…They proposed a biologic "fingerprint" of probable prior exposure to endocrine-disrupting agent. Our preliminary bioinformatics analysis suggests that the gene expression signature derived from host irradiation clusters radiation-preceded cancer in humans (77), consistent with this idea that a microenvironment "meta-profile" could be used to evaluate probable etiology. It is possible that such profiles could identify whether ER-negative breast cancer arises because lifestyle or external events deregulate stem cells or affect the composition of the microenvironment.…”
Section: Implications For Cancer Preventionsupporting
confidence: 77%
See 1 more Smart Citation
“…They proposed a biologic "fingerprint" of probable prior exposure to endocrine-disrupting agent. Our preliminary bioinformatics analysis suggests that the gene expression signature derived from host irradiation clusters radiation-preceded cancer in humans (77), consistent with this idea that a microenvironment "meta-profile" could be used to evaluate probable etiology. It is possible that such profiles could identify whether ER-negative breast cancer arises because lifestyle or external events deregulate stem cells or affect the composition of the microenvironment.…”
Section: Implications For Cancer Preventionsupporting
confidence: 77%
“…Preliminary bioinformatics analyses show that the genes represented in the irradiated host signature cluster ER-negative human breast cancer and are strongly associated with basal-like and claudin-low molecular profiles (77). Thus, common processes may underlie the prevalence of ER-negative mouse tumors in irradiated hosts and ER-negative sporadic breast cancers most prevalent in young women, AfricanAmerican women, and women irradiated as children.…”
Section: Microenvironment Shapes the Course Of Carcinogenesismentioning
confidence: 99%
“…As found previously in irradiated tissues and tumors arising in g-irradiated mice (30,31), Notch signaling was activated in K18-IHPsi (Fig. 6A).…”
Section: Z-scoresupporting
confidence: 87%
“…In a previous study, we found that gene expression profiles from g-or Si-irradiated mammary gland tissue were comparable in terms of enriching for MaSC signature and implicating NOTCH, TGFb, WNT pathways as upstream regulators (23) up to 12 weeks postirradiation. Tumors arising in hosts irradiated with low doses of sparsely ionizing radiation show a distinct gene expression profile, even though tumors occur many months postirradiation, and even when segregated by ER status (30,31). Because of insufficient number of contemporaneous tumors from g-irradiated host, we were not able to compare the quality difference at the molecular level or control for tumor marker status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation